Effects of Different Concentration of Sodium Chloride on the Growth & Yield of Okra - Salik, Abdul Walid; Malik, Hikmatullah; Alipor, Hasan (Journal of Natural Sciences – Kabul University, 2020)
An experiment was conducted in plastic pots using a randomized complete block design (RCBD) to examine the effects of saline irrigation water on the growth and fresh pod yield of okra (Abelmoschus esculentus L.). Four treatments with varying sodium chloride concentrations (0.0 mM, 5 mM, 10 mM, and 20 mM) were applied throughout the growing season. The control treatment showed 98% germination, while a significant reduction in germination was observed with increasing salinity, reaching only 53% at 20 mM. The maximum leaf length in the control treatment was 9.17 cm, while the minimum was 6.8 cm at 20 mM. Shoot height at 20 mM salinity was shorter (13.87 cm), while 5 mM had the longest shoot length (15.6 cm). Root length also decreased with increasing salinity, with the control showing 15.37 cm and 20 mM showing 8.7 cm. The control treatment yielded 6904 kg/ha of fresh pods, while the yields at 5 mM, 10 mM, and 20 mM were 6696 kg/ha, 4772 kg/ha, and 3100 kg/ha, respectively.